Community involvment in orchid conservation - Dilley, Andrew (Universidad de Costa Rica, 2015)
In 2000 the Australasian Native Orchid Society, Victorian Group Inc. (ANOS Vic) made the decision to become proactive in orchid conservation. It was appar- ent that government organisations were over stretched when it came to devoting the resources needed to protect our native orchids and that as a society we could assist in many ways.